Development of Electronic Student Worksheets Integrating Scientific Numeracy Literacy Content for Ecosystem Topics - Putri Dewi; Elvira Destiansari; Susy Amizera; Putri Setioningrum (Universitas Lambung Mangkurat, 2026)
Scientific and numeracy literacy are essential competencies for students in the 21st century, as they enable learners to interpret data, solve contextual problems, and apply scientific concepts in everyday life. However, Indonesian students continue to demonstrate relatively low achievement in these areas, partly due to the limited availability of learning resources that integrate numeracy literacy with science instruction, especially in biology topics such as ecosystems. Therefore, this study aimed to develop an electronic student worksheet integrating scientific and numeracy literacy content on the ecosystem subtopic. This study employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product was validated by three experts, while its practicality was assessed by three teachers and twelve students using Likert-scale questionnaires. The validation results showed that the electronic student worksheet achieved an average score of 91.42%, indicating a very valid category. In addition, the practicality test revealed scores of 88.79% from students and 96.35% from teachers, both categorized as very practical. These findings indicate that the developed electronic student worksheet is a feasible and practical learning resource for biology instruction. It also offers an innovative alternative for integrating scientific and numeracy literacy into ecosystem learning to better support students’ competency development.